1999
DOI: 10.1677/joe.0.163r005
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormone transport by 4F2hc-IU12 heterodimers expressed in Xenopus oocytes

Abstract: Thyroid hormone (TH) action and metabolism require hormone transport across cell membranes. We have investigated the possibility that TH are substrates of amino acid transport (System L) mediated by heterodimers of 4F2 heavy-chain (hc) and the light-chain (lc) permease IU12. Coexpression of 4F2hc and IU12 cDNAs injected into Xenopus oocytes induces saturable, Na + -independent transport of triiodothyronine (T3), thyroxine (T4) (Km of 1.8 and 6.3 µM respectively), tryptophan and phenylalanine. Induced TH and tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
35
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 26 publications
4
35
0
Order By: Relevance
“…The fact that the T 3 -uptake system in tadpole RBCs was sensitive to taurocholate and bromosulfophthalein but was insensitive to choline suggests the possibility that some of Na + -independent organic anion transporters (Abe et al 1998, Fujiwara et al 2001 are involved in the tadpole T 3 -uptake system. The K m values obtained from our studies were within the same range of those values obtained for the System T-linked T 3 -uptake system , Zhou et al 1990, McLeese & Eales 1996b, but one order of magnitude lower than those values obtained for System L (Blondeau et al 1993, Ritchie et al 1999, Ritchie & Taylor 2001) and the organic anion transporters (rat oatp2 and oatp3, human LST-1 and OATP-E; Abe et al 1998, Fujiwara et al 2001. Therefore, the T 3 -uptake system that is responsible for a major part of saturable T 3 uptake into tadpole RBCs may be the System T-linked uptake system and may be a common feature for rat, bullfrog and rainbow trout RBCs.…”
Section: Discussionsupporting
confidence: 88%
“…The fact that the T 3 -uptake system in tadpole RBCs was sensitive to taurocholate and bromosulfophthalein but was insensitive to choline suggests the possibility that some of Na + -independent organic anion transporters (Abe et al 1998, Fujiwara et al 2001 are involved in the tadpole T 3 -uptake system. The K m values obtained from our studies were within the same range of those values obtained for the System T-linked T 3 -uptake system , Zhou et al 1990, McLeese & Eales 1996b, but one order of magnitude lower than those values obtained for System L (Blondeau et al 1993, Ritchie et al 1999, Ritchie & Taylor 2001) and the organic anion transporters (rat oatp2 and oatp3, human LST-1 and OATP-E; Abe et al 1998, Fujiwara et al 2001. Therefore, the T 3 -uptake system that is responsible for a major part of saturable T 3 uptake into tadpole RBCs may be the System T-linked uptake system and may be a common feature for rat, bullfrog and rainbow trout RBCs.…”
Section: Discussionsupporting
confidence: 88%
“…7A) (6 -8, 40, 41). It was previously reported that IU12 / ASUR4, a Xenopus homolog of LAT1, accepts thyroid hormones as substrates (42); based on the double-reciprocal-plot analysis (data not shown), these modified AAs with bulky side chains are determined to be competitive inhibitors of hLAT1-mediated transport. Therefore, hLAT1's binding site may accommodate bulky side chains such as those of the thyroid hormones and melphalan.…”
Section: Discussionmentioning
confidence: 86%
“…It has been shown that the aromatic amino acids Tyr and Trp, which can be transported by both systems L and T, inhibit the uptake of T 3 in neonatal cardiomyocytes and transfected Xenopus oocytes (Everts et al 1996b, Ritchie et al 1999. Only system L is sensitive to the synthetic amino acid analogue BCH (Broer et al 1998, Ritchie et al 1999. Our results show that uptake of T 3 was not sensitive to BCH, from which we conclude that system L does not participate in uptake of T 3 in neonatal rat cardiomyocytes.…”
Section: Discussionmentioning
confidence: 44%
“…Other likely candidates for a putative accessory transport system could be members of amino acid transport systems T or L. Both system T and L are Na + independent, and both systems transport aromatic amino acids (Kragie 1994, Palacín et al 1998. It has been shown that the aromatic amino acids Tyr and Trp, which can be transported by both systems L and T, inhibit the uptake of T 3 in neonatal cardiomyocytes and transfected Xenopus oocytes (Everts et al 1996b, Ritchie et al 1999. Only system L is sensitive to the synthetic amino acid analogue BCH (Broer et al 1998, Ritchie et al 1999.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation